Building Service Experience to Attain Customer Repurchase Intention: A Moderated-Mediation Model in the Context of Student Consumer in Indonesia - Zulganef Zulganef; Irma Nilasari (DeReMa (Development Research of Management): Jurnal Manajemen, 2022)
This study aims to determine the effect of service experience on repurchase intention, by looking at the mediating role of customer satisfaction and moderation of perceived quality. This research was conducted on students at several universities who use online business applications, with a total of 250 respondents. Research data was collected online, and respondents were asked to fill out a questionnaire distributed through Google Forms. The results of this study indicate that service experience has an effect on customer satisfaction and repurchase intention. The findings of this study also indicate that customer satisfaction mediates the relationship between service experience and repurchase intention. Finally, this study looks at the moderating role of perceived quality, and finds that perceived quality can moderate the relationship between service experience and customer satisfaction, the relationship between customer satisfaction and repurchase intention, and the indirect relationship of service experience on repurchase intention through customer satisfaction. Abstrak dalam Bahasa Indonesia. Penelitian ini bertujuan untuk mengetahui pengaruh service experience terhadap repurchase intention, dengan melihat peran mediasi kepuasan pelanggan dan moderasi persepsi kualitas. Penelitian ini dilakukan pada mahasiswa di beberapa perguruan tinggi yang menggunakan aplikasi bisnis online, dengan jumlah responden sebanyak 250 orang. Data penelitian dikumpulkan secara online, dan responden diminta untuk mengisi kuesioner yang disebarkan melalui Google Forms. Hasil penelitian ini menunjukkan bahwa pengalaman layanan berpengaruh terhadap kepuasan pelanggan dan niat beli ulang. Temuan penelitian ini juga menunjukkan bahwa kepuasan pelanggan memediasi hubungan antara pengalaman layanan dan niat membeli kembali. Akhirnya, penelitian ini melihat peran moderasi persepsi kualitas, dan menemukan bahwa kualitas yang dirasakan dapat memoderasi hubungan antara pengalaman layanan dan kepuasan pelanggan, hubungan antara kepuasan pelanggan dan niat membeli kembali, dan hubungan tidak langsung dari pengalaman layanan pada niat pembelian kembali melalui kepuasan pelanggan.